The Influence of Tiktok Social Media and Destination Images on the Interest of Culinary Tourism Visits in Suryakancana Bogor on Followers @bogoreatery - Saragi, Charles Parnauli; Mulyana, Ade; Mulia, Isnan; Maulidia, Nafda (LPPM UIKA Bogor, 2024)
The Tiktok account @Bogoreatery is an account that provides information about culinary tourism in Bogor and often collaborates with culinary business owners to promote their culinary products. However, sometimes the uploaded content does not have complete information and is in accordance with the reality on ground, so that tourists who watch the content still feel dissatisfied with the information provided. Therefore, this research raises the variables of Tiktok Social Media, Destination Image and their influence on Interest in Visiting Culinary Tourism in Suryakancana among @Bogoreatery Followers. The aim of this research is to find out whether the quality of content uploaded to @Bogoreatery and the image of the destination displayed in that content can influence the increase in tourist interest in visiting. This research uses a quantitative method with a purposive random sampling data collection method on 112 respondents. The results of the research show that there is a significant positive influence on TikTok social media and destination image on interest in visiting culinary tourism in Suryakancana among @Bogoreatery followers. So it can be concluded that the social media value of TikTok has a positive influence of 0.322, and the destination image has a positive influence of 0.369.